2023
DOI: 10.11591/ijere.v12i2.22845
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of item bias in the four-tier diagnostic test using Rasch model

Abstract: The existence of item bias in a set of measuring instruments can threaten the instrument’s validity. Based on the Rasch model, this study evaluated item bias in the four-tier heat and temperature diagnostic test (4T-HTDT). This study used a cross-sectional quantitative survey method. There were 241 students selected using a stratified random sampling technique. The 4T-HTDT instrument consisted of 20 items grouped into five concept groups. Students’ conceptual understanding was grouped into five categories, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The findings discovered that the multi-dimensional model had a significantly better statistical fit than the unidimensional model through the likelihood ratio Chi-squared G 2 (𝜒 2 =21.56, df=2) [23] as well as the Akaike information criterion (AIC) [24], and Bayesian information criterion (BIC) [25] had a lower value in multidimensional constructs for assessing MP, as shown in Table 3. The research indicates that it would be appropriate to diagnose mathematical proficiency in two dimensions in the real context [26]- [28]. Additionally, the results of the correlation matrix of MAP and SLO dimensions showed that there was a correlation between the two dimensions at 0.55.…”
Section: Validity Evidencementioning
confidence: 82%
“…The findings discovered that the multi-dimensional model had a significantly better statistical fit than the unidimensional model through the likelihood ratio Chi-squared G 2 (𝜒 2 =21.56, df=2) [23] as well as the Akaike information criterion (AIC) [24], and Bayesian information criterion (BIC) [25] had a lower value in multidimensional constructs for assessing MP, as shown in Table 3. The research indicates that it would be appropriate to diagnose mathematical proficiency in two dimensions in the real context [26]- [28]. Additionally, the results of the correlation matrix of MAP and SLO dimensions showed that there was a correlation between the two dimensions at 0.55.…”
Section: Validity Evidencementioning
confidence: 82%
“…The instrument used in this research was 20 multiple-choice items on heat and temperature material developed by Sukarelawan et al (Jumadi et al, 2023). Twenty items are spread into four concept groups, namely: (1) temperature (6 items), (2) expansion (4 items), (3) the effect of heat on temperature changes and changes in form (4 items), and (4) heat and heat transfer (6 items).…”
Section: Methodsmentioning
confidence: 99%
“…Various methods of analyzing students' conceptual understanding have been widely used. For example, interview methods (Fuchs & Czarnocha, 2016;Jankvist & Niss, 2018), multiple-choice (Dulger, 2017;Kusairi et al, 2022), two-level multiple choice (Atchia et al, 2022;Onder-Celikkanli & Tan, 2022;Wang et al, 2022), three-level multiple choice (Prodjosantoso et al, 2019;Yeo et al, 2022), and fourlevel multiple choice (Astuti et al, 2023;Atmaca Aksoy & Erten, 2022;Jumadi et al, 2023;Taban & Kiray, 2022). The approach to analyzing conceptual understanding is oriented to classical test theory (CTT).…”
Section: Introductionmentioning
confidence: 99%
“…Racking analysis is used to analyze what types of skills change [29], [32], [33]. Grouping students' skill levels refers to the Logit Value of Person (LVP) [34], and grouping the difficulty level of skill aspects refers to the Logit Value of Item (LVI) [35], as shown in Table 1 and Table 2.…”
Section: Methodsmentioning
confidence: 99%